Comparation of metering LPG Truck loading and metering accuracy at site Shylhet Gas Field project, Bangladesh - Sumarno (Action Research Literate, 2024)
PT. Istana Karang Laut company is located in Jakarta with a truly international team of highly motivated and experienced specialists, IKL offers a wide range of products and project capabilities and is able to execute projects either for lump-sum EPC (Engineering, Procurement, Construction) or individual Process Equipment as well as O&M contracts (Operations and Maintenance). This research aims to examine and compare the measurement methods used in the LPG truck loading process with the measurement accuracy level carried out at the Shylhet Gas Field project site in Bangladesh. Use method statistical quality control for trouble shooting LPG truck loading metering is to improve quality thereby reducing manufacturing costs, scrap, rework, rescheduling, increase consumer confidence and tighten specification limits and increase productivity and production yields. The conclusions and recommendations resulting from this study include meter adjustments to reduce systematic and random errors, as well as measures to prevent random errors in the future. Meter adjustments are made by calculating the new meter factor based on the average of the observed mismatches. In order to reduce random errors, it is recommended to collect as many samples as possible, pay attention to the condition of the truck and the environment before each load, as well as improve the operator's skills in reading the measuring instrument to avoid parallax errors.